2019
DOI: 10.1186/s12864-018-5336-z
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of B-BOX gene family and their expression profiles under hormonal, abiotic and metal stresses in Poaceae plants

Abstract: BackgroundB-box (BBX) proteins play important roles in plant growth regulation and development including photomorphogenesis, photoperiodic regulation of flowering, and responses to biotic and abiotic stresses.ResultsIn the present study we retrieved total 131 BBX members from five Poaceae species including 36 from maize, 30 from rice, 24 from sorghum, 22 from stiff brome, and 19 from Millet. All the BBX genes were grouped into five subfamilies on the basis of their phylogenetic relationships and structural fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 48 publications
5
46
0
1
Order By: Relevance
“…4 ). This result is similar to those from studies of BBX gene family evolution in pear [ 33 ], rice [ 34 ], tomato [ 35 ], maize, sorghum, stiff brome and millet [ 38 ]. Moreover, the segmentally duplicated gene pairs, (e.g., VviBBX21a / VviBBX21b ) comprised the same group and exhibited similar exon-intron structures and motifs (Fig.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…4 ). This result is similar to those from studies of BBX gene family evolution in pear [ 33 ], rice [ 34 ], tomato [ 35 ], maize, sorghum, stiff brome and millet [ 38 ]. Moreover, the segmentally duplicated gene pairs, (e.g., VviBBX21a / VviBBX21b ) comprised the same group and exhibited similar exon-intron structures and motifs (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…Detailed information about these genes, including gene ID, accession numbers, structural group classification, and physiological and biochemical properties of the encoded protein are given in Table 1 . The number of BBX family genes was the same as found in pear [ 33 ] and was less than in Arabidopsis [ 4 ], rice [ 34 ], tomato [ 35 ], potato [ 36 ], apple [ 37 ] and maize [ 38 ], but higher than eight other plant species [ 38 , 39 ]. We also found that the largest number of BBX members in a plant was 64 from apple, while the least was 19 in millet (Additional file 11 : Fig.…”
Section: Discussionmentioning
confidence: 85%
“…The function of BBX proteins in abiotic stresses is still poorly understood. To date, in the Poaceae species, the OsBBX1, OsBBX2, OsBBX8, OsBBX19 and OsBB24 genes have been linked to abiotic stress responses, including drought, through changes in their expression profiles, which potentially signify roles in the plants' stress response (Shalmani et al 2019). In addition, a few BBX genes have been functionally annotated with regard to drought stress.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the diversification of their protein sequences and structures, zinc-finger genes are further classified into several distinct subfamilies [3]. A subgroup of zinc-finger proteins containing B-box (BBX) conserved domains, which are thought to be involved in protein-protein interactions, is designated as the BBX family and is highly conserved across all multicellular species [4,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%